Calculation of Start-Up Time of Passive Catalytic Hydrogen Recombiner of Localization Safety System of a Nuclear Power Plant Equipped with VVER - V. V. Sorokin (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The hydrogen removal system ensures hydrogen safety. At a VVER nuclear power plant, it consists of passive catalytic hydrogen recombiners. The calculation of devices is of great importance for safety justification, since the complex conditions of an accident at a power unit are not reproducible in experiments. The recombiner consists of a casing and a cassette with catalytic elements, the design of which ensures the passage of a gaseous medium through the device. Upon contact with the catalyst, a chemical reaction of hydrogen and oxygen compounds occurs, accompanied by the release of heat; as a result, the concentration of hydrogen under the shell decreases. The problem is starting from a cold state since the activity of the cold catalyst is low, and the thrust is not observed until the catalyst is heated and a column of warm gas is formed inside the device. The transition from the cold state to the working state takes a certain time, during which the recombiner performance is below nominal. The start-up time is a parameter that is important in terms of safety. The article calculates the start-up time of a hydrogen recombiner with a catalytic block in the form of equidistant parallel catalytic plates. Local cross-sectional averages and transmission coefficients are used, the latter taking into account the influence of free convection and chemical reaction. The gas velocity is determined by the balance of buoyant and resistance forces. The calculated data and the data known from the scientific and technical literature coincide satisfactorily. As a conservative estimate of the start-up time of the recombiner, it is recommended to use the value of 300 s. An increase in temperature practically does not affect the start of the recombiner with an active catalyst, an increase in the concentration of hydrogen accelerates the start, and a decrease in pressure slows it down. The results obtained in the study can be used in the justification of the safety of VVER nuclear power plants and the examination of reports on the justification of the safety of power units.